Biaxially oriented polyester film for electrodes, laminated film for electrodes, electrodes, and method for manufacturing biaxially oriented polyester film for electrodes

JP2025030167APending Publication Date: 2025-03-07TORAY INDUSTRIES INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023135221
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-23
Publication Date
2025-03-07

AI Technical Summary

Benefits of technology

【0011】 本発明によれば、電極基材の薄膜化が進められている中、金属膜を積層したフィルムを電極基材構成とすることによって、従来、金属箔の圧延による薄膜化にて課題となっていたピンホールを無くし、加工張力にも耐えられるようにするとともに、金属膜を積層した際の金属膜とフィルムとの密着性を向上し、かつ巻き取りなどの曲げが加わった前後でも電気抵抗特性のよい電極用二軸配向ポリエステルフィルムおよびそれを用いた電池の電極フィルムを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025030167000001
    Figure 2025030167000001
  • Figure 2025030167000002
    Figure 2025030167000002
Patent Text Reader

Abstract

To provide a biaxially oriented polyester film for an electrode, and an electrode film for a battery using the same, in which while an electrode base material is getting thinner, technologies for eliminating pinholes which are an issue when thinning metal foil by rolling, and improving a resistance to processing tension, also improving an adhesion property between a metal film and a film when laminated, and improving electrical resistance properties even before and after bending such as winding are developed by using a film laminated with a metal film as an electrode base material structure.SOLUTION: There is provided a multi-layer film having a B-layer mainly composed of polyester and a surface layer (layer A) mainly composed of polyester, which is a biaxially oriented polyester film for an electrode, which satisfies following requirements (1) to (4): (1) a thickness of the layer A is 0.1 μm or more and less than 1.5 μm; (2) a total thickness of the film is 1.5 μm or more and 15 μm or less; (3) an intrinsic viscosity (IV, unit:dl / g) of the layer A is 0.65 to 1.20; and (4) a crystallinity of the entire film as determined by differential scanning calorimetry is 30.0 to 50.0%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a biaxially oriented polyester film for an electrode, a laminated film for an electrode, an electrode, and a method for producing a biaxially oriented polyester film for an electrode. [Background technology]

[0002] In recent years, the promotion of renewable energy has become increasingly important as a measure to simultaneously reduce greenhouse gas emissions and ensure energy security. In particular, it is difficult to ensure stable output from solar and wind power generation because the amount of power generated depends on weather conditions, and lithium-ion secondary batteries are effectively used in renewable energy power generation facilities.

[0003] Recently, lithium-ion secondary batteries have started to be used in automobiles, including electric vehicles (EVs) and plug-in hybrid electric vehicles (PHEVs), and are also widely used in small electronic devices such as mobile phones, laptops, and portable music players. To miniaturize lithium-ion secondary batteries in line with the development of the portable electronic device market, it is necessary to improve their performance and reliability.

[0004] The electrodes used in these lithium-ion secondary batteries have the ability to absorb (absorb) and release (discharge) lithium in both the positive and negative electrodes, and lithium ions move to the negative electrode during charging and to the positive electrode during discharging. Each electrode must be in contact with an electrolyte or solid electrolyte to exchange lithium ions between the electrodes, and metal foils with a thickness of about 10 to 30 μm have traditionally been used as the substrate for the electrodes.

[0005] As a new material to replace metals, a structure in which a conductive thin film layer of metal or the like is provided on the surface of a biaxially oriented polyester film can be mentioned, and it has been proposed to use this material as an electrode substrate with a current collector function (Patent Documents 1 to 3). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Application Publication No. 10-40919 [Patent Document 2] Japanese Patent Application Publication No. 10-40920 [Patent Document 3] JP 2014-220187 A Summary of the Invention [Problem to be solved by the invention]

[0007] However, in recent years, as the volumetric energy density has improved due to the increased capacity of lithium-ion secondary batteries, it has become necessary to improve the weight energy density by miniaturizing the batteries, and efforts are being made to make electrode substrates thinner. However, the conventional technology of thinning the substrate by rolling metal foil has posed issues such as the generation of pinholes that cause the coating liquid to leak through, or the substrate being too weak to withstand the processing tension, resulting in cuts or wrinkles.

[0008] In view of the above, an object of the present invention is to provide a biaxially oriented polyester film for electrodes and a battery electrode film using the same, which, by using a film laminated with a metal film as the electrode substrate in the current trend toward thinner electrode substrates, eliminates pinholes that have been an issue in the past when thinning metal foils by rolling them, enables the film to withstand processing tension, improves adhesion between the metal film and the film when the metal film is laminated, and has good electrical resistance characteristics even before and after bending, such as when wound up. [Means for solving the problem]

[0009] As a result of extensive investigations aimed at solving the above problems, it was found that the above problems could be solved by using a biaxially oriented film having specific physical properties as a substrate film, which led to the present invention.

[0010] That is, a preferred embodiment of the electrode film of the present invention has the following configuration. 1. A biaxially oriented polyester film for electrodes, which is a multilayer film having a B layer mainly composed of polyester and a surface layer (A layer) mainly composed of polyester, and which satisfies the following requirements (1) to (4). (1) The thickness of layer A is 0.1 μm or more and less than 1.5 μm (2) The total thickness of the film is 1.5 μm or more and 15 μm or less. (3) The intrinsic viscosity (IV, unit dl / g) of layer A is 0.65 to 1.20 (4) The crystallinity of the entire film is 30.0 to 50.0% as determined by differential scanning calorimetry using the following method: <Measurement method> Measure by heating from 25°C to 300°C at a heating rate of 20°C / min. The degree of crystallinity (Χc) is calculated from the differential scanning calorimetry chart obtained using the heat of crystalline fusion (ΔHm) and the heat of cold crystallization (ΔHc) according to the following formula. Χc=(ΔHm-ΔHc) / ΔHm0 Here, ΔHm0 is 140.10 J / g, which is the heat of fusion of perfectly crystalline PET. 2. The biaxially oriented polyester film for electrodes according to 1., wherein the intrinsic viscosities of at least one of the surface layers (layer A) and layer B satisfy the following relationship: Intrinsic viscosity of surface layer (layer A) > Intrinsic viscosity of layer B 3. The biaxially oriented polyester film for an electrode according to 1. or 2., wherein at least one of the surface layers (layer A) has a three-dimensional center surface average roughness (SRa) of 40 to 80 nm. 4. The biaxially oriented polyester film for an electrode according to any one of 1. to 3., wherein at least one of the layers A contains particles containing Al element. 5. A laminate film for an electrode, comprising the biaxially oriented polyester film for an electrode according to any one of 1. to 4. and an organic layer on at least one surface of the biaxially oriented polyester film for an electrode. 6. An electrode having the biaxially oriented polyester film for electrodes according to any one of 1. to 4. 7. A method for producing a biaxially oriented polyester film for electrodes, which is a multilayer film having a B layer mainly composed of polyester and a surface layer (A layer) mainly composed of polyester, and which satisfies the following requirements (a) to (d): (a) The thickness of layer A is 0.1 μm or more and less than 1.5 μm (b) The total thickness of the film is 1.5 μm or more and 15 μm or less. (c) Layer A is formed by melt extruding a resin raw material with an intrinsic viscosity (IV, unit dl / g) of 0.65 to 1.20. (d) The crystallinity of the entire film as determined by differential scanning calorimetry using the following method 30.0~50.0% <Measurement method> Measure by heating from 25°C to 300°C at a heating rate of 20°C / min. The degree of crystallinity (Χc) is calculated from the differential scanning calorimetry chart obtained using the heat of crystalline fusion (ΔHm) and the heat of cold crystallization (ΔHc) according to the following formula. Χc=(ΔHm-ΔHc) / ΔHm0 Here, ΔHm0 is 140.10 J / g, which is the heat of fusion of perfectly crystalline PET. Effect of the Invention

[0011] According to the present invention, while electrode base materials are being made thinner, by using a film laminated with a metal film as the electrode base material, it is possible to eliminate pinholes that have been an issue in the past when thinning metal foils by rolling them, to enable the film to withstand processing tension, to improve the adhesion between the metal film and the film when the metal film is laminated, and to provide a biaxially oriented polyester film for electrodes that has good electrical resistance characteristics before and after bending such as when wound up, and an electrode film for a battery using the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will be described in detail below.

[0013] The electrode film of the present invention is preferably a biaxially oriented film. A biaxially oriented film is produced by stretching an unstretched resin sheet or film in two directions, the longitudinal direction and the transverse direction, and shows a biaxially oriented pattern in wide-angle X-ray diffraction. As a method for stretching in the biaxial direction, either a sequential biaxial stretching method or a simultaneous biaxial stretching method can be used.

[0014] The electrode film of the present invention is preferably a biaxially oriented polyester film made of polyester.

[0015] The polyester constituting the biaxially oriented polyester film for electrodes of the present invention is a general term for polymers in which ester bonds are the main bonding chains of the main chain, but from the standpoints of heat resistance, film formability, etc., those in which ethylene terephthalate and / or ethylene naphthalate units are the main constituent components are preferred.

[0016] The polyester of the present invention may contain other copolymerization components within the range that does not impair the properties, and examples of the dicarboxylic acid components that can be used include aromatic dicarboxylic acids such as diphenyldicarboxylic acid, diphenylsulfonedicarboxylic acid, diphenoxyethanedicarboxylic acid, 5-sodium sulfoisophthalic acid, phthalic acid, and isophthalic acid, aliphatic dicarboxylic acids such as oxalic acid, succinic acid, eicosanoic acid, adipic acid, sebacic acid, dimer acid, dodecanedioic acid, maleic acid, and fumaric acid, alicyclic dicarboxylic acids such as cyclohexynedicarboxylic acid, oxycarboxylic acids such as p-oxybenzoic acid, and polyfunctional acids such as trimellitic acid and pyromellitic acid. On the other hand, examples of the glycol components that can be used include aliphatic glycols such as propanediol, butanediol, pentanediol, hexanediol, neopentyl glycol, and triethylene glycol, alicyclic glycols such as cyclohexanedimethanol, aromatic glycols such as bisphenol A and bisphenol S, diethylene glycol, and polyalkylene glycol. Furthermore, polyethers such as polyethylene glycol and polytetramethylene glycol may be copolymerized.

[0017] These dicarboxylic acid components and glycol components may be used in combination of two or more kinds, and two or more kinds of polyesters may be blended and used.

[0018] In the present invention, the polyester is preferably one having ethylene terephthalate and / or ethylene naphthalate units as the main constituents from the viewpoint of heat resistance and film-forming properties, and more preferably one having ethylene terephthalate units as the main constituents. "Having ethylene terephthalate and ethylene naphthalate units as the main constituents" means that 100 mol % of the diol components of the polyester contains 70 mol % or more of ethylene glycol components and 100 mol % of the dicarboxylic acid components of the polyester contains 70 mol % or more of terephthalic acid and / or naphthalenedicarboxylic acid components in total. "Having ethylene terephthalate or ethylene naphthalate units as the main constituents" means that 100 mol % of the diol components of the polyester contains 70 mol % or more of ethylene glycol components and 100 mol % of the dicarboxylic acid components of the polyester contains 70 mol % or more of terephthalic acid or naphthalenedicarboxylic acid components.

[0019] Furthermore, the biaxially oriented polyester film for electrodes may contain polyethylene naphthalate while containing polyethylene terephthalate. In this case, it is preferable that the content is 0.5% by mass or more and 20% by mass or less from the viewpoint of heat resistance. More preferably, it is 1% by mass or more and 10% by mass or less. Even more preferably, it is 3% by mass or more and 5% by mass or less. If the content of polyethylene naphthalate is less than 0.5% by mass, the effect of improving heat resistance may not be effective. If the content of polyethylene naphthalate exceeds 20% by mass, the compatibility of polyethylene terephthalate and polyethylene naphthalate is poor, it becomes difficult to form a crystal structure, and the orientation, heat resistance, and moist heat resistance may be reduced due to the increase in the amorphous structure. The biaxially oriented polyester film is preferably a biaxially oriented polyethylene terephthalate film or a biaxially oriented polyethylene naphthalate film, and it is more preferable that the biaxially oriented polyester film is a biaxially oriented polyethylene terephthalate film. In addition, it is preferable that the melting point of the biaxially oriented polyester film for electrodes is 250°C or more and 280°C or less. By setting the melting point to 250° C. or higher, the durability against the heat load during processing is improved. Furthermore, various additives, such as a heat stabilizer, an oxidation stabilizer, a weather stabilizer, an ultraviolet absorber, an organic lubricant, a pigment, a dye, organic or inorganic fine particles, a filler, a nucleating agent, etc., may be blended into this polyester resin within a range that does not impair the effects of the present invention.

[0020] The particles that can be contained in the biaxially oriented polyester film for electrodes of the present invention include inorganic particles such as particles, aggregates, silicon dioxide particles, calcium carbonate particles, alumina particles, titanium oxide particles, barium sulfate particles, aluminum silicate particles, calcium phosphate particles, mica, kaolin, clay, etc., which are generated during polymerization by various nucleating agents, and organic particles such as crosslinked polystyrene particles, acrylic particles, imide particles, silicone particles, etc., or mixtures thereof. Among them, alumina particles, aluminum silicate particles, mica, kaolin, clay, etc. containing Al element are more preferable. These particles have good compatibility with metals, especially aluminum, during metal deposition, and have strong adhesion. In addition, since it has the effect of hardening the film surface, it prevents damage to the film surface when evaporated metal particles land on the film surface, and the metal particles are regularly arranged, making the deposition film uniform, thereby improving the conductivity. From this point of view, it is more preferable that the biaxially oriented polyester film for electrodes contains alumina particles. This is because alumina particles have a high Mohs hardness of 8 or more. Among them, it is particularly preferable that the biaxially oriented polyester film for electrodes contains at least one type of particles selected from the group consisting of γ-alumina, δ-alumina, and θ-alumina. In addition, by using silicon dioxide particles and / or calcium carbonate particles in combination, the transportability during roll processing of the biaxially oriented polyester can be improved. These inorganic particles are preferably mixed with particles generated during polymerization by various nucleating agents.

[0021] The particle size of the particles contained in the biaxially oriented polyester film for electrodes is not particularly limited, but the average particle size measured by the sedimentation method or the light scattering method is preferably 0.01 to 8.0 μm, more preferably 0.03 to 4.0 μm. In particular, for particles containing Al element, the particle size is preferably 0.01 to 2.0 μm. The particle content is preferably 0.01 to 1.0 mass% of the entire film, more preferably 0.05 to 0.5 mass%.

[0022] The polyester constituting the biaxially oriented polyester film for electrodes of the present invention preferably has a diethylene glycol content (DEG content) of 1.5% by mass or less. More preferably, it is 1.2% by mass or less, and even more preferably, it is 1.0% by mass or less. By setting the diethylene glycol content in the film within the above-mentioned range, the random amorphous portion is reduced, so that the deposited film becomes uniform when deposited, and the electrode performance can be stabilized. Furthermore, the heat resistance of the film is reduced due to the heat history of the polyester film in the deposition process, and the film stretches against an external force in the subsequent processing process, causing wrinkles, or the running property of the film becomes unstable, and the processability is deteriorated. In addition, the method of adjusting the DEG content includes a method of shortening the polymerization time, a method of reducing the amount of antimony compounds, germanium compounds, titanium compounds, etc. used as polymerization catalysts, a method of combining liquid phase polymerization and solid phase polymerization, and a method of containing an alkaline component. For example, when using only dimethyl terephthalate as the precursor of the dicarboxylic acid component and adding potassium hydroxide as an alkaline component to adjust the DEG amount, a polyester resin with a DEG amount of 0.01% by mass or more and 1.5% by mass or less can be obtained by adjusting the amount of potassium hydroxide to 0.01 parts by mass or more and 0.10 parts by mass or less per 100 parts by mass of dimethyl terephthalate.

[0023] The biaxially oriented polyester film for electrodes of the present invention has a B layer mainly made of polyester and a surface layer (A layer) mainly made of polyester. Although details will be described later, it is preferable to use the A layer as a layer on which a metal film is laminated, and it is more preferable to use the A layer as a layer on which a metal film of 0.5 μm or more is laminated. On the other hand, the B layer can function as a layer that imparts stretchability during film formation and flexibility during film processing. Incidentally, "mainly made of" means that the layer contains 70% by mass or more of polyester. In addition, it is preferable that the polyester is as described above.

[0024] The biaxially oriented polyester film for electrodes of the present invention may have a two-layer structure of A / B, a three-layer structure of A / B / A, or a multi-layer structure of more than one layer, but the A layer must be the surface layer. Here, / indicates that the layers are laminated. These laminate structures can be produced as laminated films by coextrusion.

[0025] In addition, although details will be described later, a surface layer having a thickness of 0.1 μm or more and less than 1.5 μm, an intrinsic viscosity of 0.65 to 1.20, and mainly composed of polyester is defined as layer A. When the surface layers on both sides correspond to layer A, each is treated as layer A, and the other layer mainly composed of polyester is defined as layer B. Note that layer B may be composed of multiple layers, and these multiple layers are collectively regarded as layer B and the physical properties are measured.

[0026] The biaxially oriented polyester film for electrodes of the present invention preferably has a total thickness of 1.5 μm or more and 15 μm or less. By making the total thickness 1.5 μm or more, even when a minute foreign object enters the battery, there is partial stress concentration, and the battery operating temperature is high, holes are unlikely to be formed in the electrode film, and efficiency reduction due to deformation of the electrode can be suppressed even at high operating temperatures. From the same viewpoint, it is more preferable that it is 2.0 μm or more, and even more preferable that it is 5.0 μm or more. In addition, by making the total thickness 15 μm or less, the weight of the electrode can be reduced, which can contribute to improving the energy density of the battery. From the same viewpoint, it is more preferable that it is 13 μm or less, more preferably 6.9 μm or less, and particularly preferably less than 6.5 μm. The total thickness is determined by the method described in the examples.

[0027] The thickness of the surface layer (A layer) of the film of the present invention is preferably 0.1 μm or more and less than 1.5 μm, more preferably 0.1 μm or more and 1.0 μm or less. If the thickness of A layer is 1.5 μm or more, it becomes difficult to form surface protrusions due to added particles, especially particles containing Al element with a small particle size, so that the target surface roughness cannot be achieved, and the adhesion with the metal film may be deteriorated. On the other hand, if the thickness of A layer is less than 0.1 μm, the particles contained in A layer are likely to fall off, and the abrasion resistance of the film may be deteriorated. In addition, the fallen particles and abrasion powder may get between the film and the metal film, and holes may be formed in both the film and the metal film during press processing.

[0028] The layers A and B may be made of the same or different polyesters. Particles may also be added.

[0029] The intrinsic viscosity (measured in orthochlorophenol at 25°C) of the biaxially oriented polyester film for electrodes of the present invention is preferably 0.50 to 1.20 dl / g, more preferably 0.55 to 1.15 dl / g, and even more preferably 0.60 to 1.10 dl / g, which is suitable for the present invention.

[0030] The intrinsic viscosity of the surface layer (A layer) is preferably 0.65 to 1.20 dl / g. More preferably, it is 0.70 to 1.10 dl / g, further preferably 0.80 to 1.00 dl / g, and particularly preferably 0.91 dl / g or more. By setting the intrinsic viscosity of the surface layer (A layer) within the above range, the molecular chain is sufficiently long, and the molecular mobility in a moist heat resistant environment is suppressed, improving the heat resistance, and the hydrolysis resistance is also improved by reducing the terminal portion. Furthermore, since the molecular chain is long, the molecular mobility is low even when the polyester film is heated during the deposition process, and the deposition film can be made uniform, the conductivity of the deposition film is improved, and the electrode performance is stabilized. In addition, when the A layer is present on both sides, it is sufficient that the intrinsic viscosity of at least one A layer is 0.65 to 1.20 dl / g, and it is more preferable that the intrinsic viscosity of both A layers is 0.65 to 1.20 dl / g.

[0031] From the same viewpoint as above, the layer A is preferably formed by melt-extruding a resin raw material having an intrinsic viscosity (IV, unit: dl / g) of 0.65 to 1.20.

[0032] In the intrinsic viscosity of the biaxially oriented polyester film for electrodes of the present invention, in the relationship between at least one of the surface layers (A layer) and B layer, it is preferable that the intrinsic viscosity of the surface layer (A layer) is greater than the intrinsic viscosity of B layer. In this embodiment, the intrinsic viscosity of B layer is reduced, which gives the film flexibility and makes it easier to handle in post-processing such as deposition processing, printing processing, and lamination processing. In addition, the film does not become excessively hard, and even if the film is bent by winding after the metal layer is provided, cracks and peeling of the metal layer can be suppressed. In addition, the difference between the intrinsic viscosity of the surface layer (A layer) and the intrinsic viscosity of B layer is not particularly limited, but it is more preferable that it is 0.05 dl / g or more.

[0033] The intrinsic viscosity of the B layer is preferably 0.50 to 0.70 dl / g, more preferably 0.55 to 0.70 dl / g, and even more preferably 0.58 to 0.68 dl / g, from the viewpoint of stretchability during film formation and flexibility during film processing. Usually, it is preferable that it is 0.60 dl / g or more, but since the intrinsic viscosity of the A layer is high, it is possible to lower the intrinsic viscosity of the B layer. There is no particular limitation on the method for adjusting the intrinsic viscosity, but examples include a method of performing melt polymerization or solid-phase polymerization in a batch or continuous manner at the stage of polyester raw materials, as in the case of commonly used polyesters. The solid-phase polymerization method is more preferable because the polymerization time is relatively short and the carboxyl end group concentration can be reduced with an increase in viscosity, and it can be adjusted by the solid-phase polymerization time and the amount of catalyst added. In addition, when the polyester raw materials are melt-formed into a polyester film, hydrolysis and thermal decomposition due to the moisture remaining in the molten state proceed, so it is preferable that the intrinsic viscosity of the polyester raw materials used as the raw materials for the film before melt extrusion is higher than the target value of the intrinsic viscosity of the polyester resin constituting the film. Therefore, even if the intrinsic viscosity of the polyester resin of the film raw material is made higher than the target value of the intrinsic viscosity of the polyester resin constituting the film, it is preferable that the difference is small, and the intrinsic viscosity of the polyester resin of the film raw material is preferably 0.05 to 0.15 higher than the target value of the intrinsic viscosity of the polyester resin constituting the film. Note that the intrinsic viscosity is determined by the method described in the Examples.

[0034] In the biaxially oriented polyester film for electrodes of the present invention, the three-dimensional center plane average roughness (SRa) of at least one of the surface layers (A layer) is preferably 40 to 80 nm. More preferably, it is 50 to 80 nm. The three-dimensional center plane average roughness (SRa) here is a parameter of three-dimensional surface roughness obtained by a measurement method described later. By setting the three-dimensional center plane average roughness (SRa) within the above-mentioned range, the adhesive surface area with the metal film increases when laminating with the metal film or vapor deposition, and sufficient adhesiveness as an electrode can be obtained. Furthermore, the slipperiness is also good, making it easy to wind up in the processing step and suppressing the occurrence of blocking. On the other hand, if the three-dimensional center plane average roughness (SRa) is less than 40 nm, the adhesive surface area with the metal film decreases, and sufficient adhesiveness as an electrode may not be obtained. In addition, if it exceeds 80 nm, the protrusions may damage or dent the metal film during winding during metal film processing, thereby reducing the electrode performance.

[0035] The biaxially oriented polyester film for electrodes of the present invention preferably has a breaking strength of 200 MPa or more in both the longitudinal direction and the width direction. More preferably, both are 210 MPa or more. If it is less than 200 MPa, the puncture strength may decrease. If either one of them is less than 200 MPa, the film may be easily broken from that direction and the puncture strength may decrease.

[0036] The puncture strength (puncture resistance) of the biaxially oriented polyester film for electrodes in the present invention is preferably 0.25 N / μm or more. More preferably, it is 0.30 N / μm or more, and even more preferably, it is 0.35 N / μm or more. If it is less than 0.25 N / μm, holes may easily form when pressed due to the inclusion of foreign matter.

[0037] The biaxially oriented polyester film for electrodes of the present invention preferably has a strength of 110 MPa or more at 5% elongation in the longitudinal direction. More preferably, it is 120 MPa or more. If the strength at 5% elongation in the longitudinal direction is less than 110 MPa, wrinkles may occur due to the process tension during the transport step after deposition in the deposition step, or the substrate film may stretch, making the deposited film prone to cracking or cracking, which may deteriorate the electrode performance.

[0038] The method for setting the breaking strength and the strength at 5% elongation within the above-mentioned range is not particularly limited, but examples include a method of adjusting the stretching temperature and stretch ratio in the longitudinal stretching process. In this case, if the film ends are heated using an infrared heater for end heating, the longitudinal stretching process is stabilized and becomes easier to control. At this time, since each strength is affected by the stretching temperature, stretch ratio, and temperature and time of the heat setting treatment in the transverse stretching process, it is preferable to balance each strength so that it falls within the range.

[0039] The polyester film constituting the biaxially oriented polyester film for electrodes of the present invention preferably has a planar orientation coefficient (fn) of 0.155 to 0.168. More preferably, it is 0.158 to 0.165. Within the above range, the orientation of the film is good, and it is less likely to decrease in strength or stretch due to external force, and the suitability for deposition processing is good. In addition, the adhesion to the deposited film is good, and peeling and falling off of the deposited film can be suppressed in the processing step after deposition. If it is less than 0.155, problems such as wrinkles are likely to occur during processing, and if it exceeds 0.168, the deposited film is likely to peel off due to cleavage of the film, etc., and problems during processing may be likely to occur.

[0040] The degree of crystallinity of the polyester constituting the biaxially oriented polyester film for electrodes of the present invention is preferably 30.0 to 50.0% throughout the film. By making the degree of crystallinity 30% or more, the heat resistance and dimensional stability are improved, and the deposited film can be made uniform during deposition, resulting in improved electrode characteristics. In addition, by making the degree of crystallinity 50% or less, embrittlement of the film surface can be suppressed, and defects in the deposited film can be suppressed in the transport system after deposition. The degree of crystallinity is determined by the following method. <Measurement method> Measure by heating from 25°C to 300°C at a heating rate of 20°C / min. The degree of crystallinity (Χc) is calculated from the differential scanning calorimetry chart obtained using the heat of crystalline fusion (ΔHm) and the heat of cold crystallization (ΔHc) according to the following formula. Χc=(ΔHm-ΔHc) / ΔHm0 Here, ΔHm0 is 140.10 J / g, which is the heat of fusion of perfectly crystalline PET.

[0041] When there are a plurality of crystal melting peaks or cold crystallization peaks, the calorific value is determined from the peak with the maximum heat of crystal melting or maximum heat of cold crystallization.

[0042] The degree of crystallinity of the entire film can be controlled to 30.0 to 50.0%, for example, by adjusting the heat setting temperature to cause thermal crystallization, or by adjusting the temperature and stretching ratio during stretching to cause oriented crystallization.

[0043] In the biaxially oriented polyester film for an electrode of the present invention, at least one of the A layers preferably contains particles containing Al element.

[0044] Preferred examples of particles containing Al element include alumina particles, aluminum silicate particles, mica, kaolin, clay, and the like. These particles have good compatibility with metals, especially aluminum, during metal deposition, and have strong adhesion. In addition, since they have the effect of hardening the film surface, they prevent damage to the film surface when evaporated metal particles land on the film surface, and the metal particles are regularly arranged, making the deposited film uniform, thereby improving the conductivity. From this point of view, it is more preferable that at least one of the A layers contains alumina particles. This is because alumina particles have a high Mohs hardness of 8 or more. Among them, it is particularly preferable that at least one of the A layers contains at least one type of particle selected from the group consisting of γ-alumina, δ-alumina, and θ-alumina. In addition, by containing silicon dioxide particles and / or calcium carbonate particles, the transportability during roll processing of the biaxially oriented polyester can be improved.

[0045] The particle diameter of the particles contained in at least one of the layers A is preferably 0.01 to 2.0 μm. The particle diameter is determined from a cross-sectional image of the layer A and refers to the median diameter counted for the diameter of a circle having an area equivalent to the particle diameter. The content of the particles is preferably 0.01 to 1.0 mass % and more preferably 0.05 to 0.5 mass % relative to the layer A.

[0046] The biaxially oriented polyester film for electrodes of the present invention preferably has an average crystal grain size (χc) of 5.0 to 8.0 nm throughout the film, more preferably 5.3 to 6.8 nm. When χc is 5.0 or more, the deposited film becomes uniform when deposited, and the adhesion between the film and the deposited film becomes good, thereby improving the electrode performance. From the viewpoint of productivity and film strength, χc is preferably 8.0 nm or less, but if it exceeds 6.8 nm, the film may become brittle and the puncture strength may decrease. There is no particular limitation on the method of controlling χc, but examples include a method of controlling the crystallization of the polyester resin by heat setting conditions, etc. For example, if the heat setting temperature after stretching is increased or the heat setting time is extended, the crystallization of the polyester resin can be promoted, so that χc tends to increase. On the other hand, if the heat setting temperature is too high or the heat setting temperature is too long, the crystallized material melts, so that χc tends to decrease. A film having a desired χc value can be obtained by appropriately adjusting the heat setting temperature and time according to the polyester resin constituting the polyester film.

[0047] When the biaxially oriented polyester film for electrodes of the present invention is formed by vapor deposition of a metal layer, it becomes a uniform vapor deposition film and stable resistance characteristics can be obtained. In addition, when it is laminated with a metal foil, the metal foil thinned by rolling has small pinholes, but by laminating it, the pinholes are blocked to prevent leakage and short circuits, and safety can be obtained, so it is preferably used for electrodes, and more preferably used for battery electrodes. "Used for electrodes" refers to electrodes used for positive and negative electrodes of batteries, such as primary batteries and secondary batteries such as lithium ion batteries, and according to the present invention, stable resistance characteristics can be obtained, which can lead to improved battery performance, such as high output and long life.

[0048] The lamination method of the metal layer can be a method of laminating a metal foil by wet lamination or dry lamination, or a deposition method, sputtering method, ion plating method, plasma vapor phase epitaxy (CVD), etc. However, in consideration of productivity, lamination with a metal foil and vacuum deposition method are the most excellent at present. As a heating means of a vacuum deposition apparatus using the vacuum deposition method, an electron beam heating method, a resistance heating method, and an induction heating method are preferable. In addition, the thickness of the metal layer is generally preferably in the range of 1 to 10 μm, and more preferably in the range of 2 to 8 μm. If the film thickness is in the above range or more, the flexibility of the deposited thin film is lost, and it becomes easier to suppress the occurrence of cracks, pinholes, etc. in the thin film due to external forces such as bending and pulling after film formation (in post-processing steps, etc.), which may deteriorate the electrode performance. On the other hand, if the film thickness is in the above range or less, the conductivity decreases, and the electrode characteristics may deteriorate.

[0049] A preferred embodiment of the method for producing an electrode film of the present invention will be specifically described below, although the present invention is not limited to the following production method.

[0050] The polyester resin used in the electrode film of the present invention preferably has a melting point of 250° C. or higher in terms of heat resistance and film formability. In addition, a commercially available polyester resin can be used as is, but it may also be produced via a polycondensation reaction as described below and used.

[0051] 0.09 parts by mass of magnesium acetate and 0.03 parts by mass of antimony trioxide are added to a mixture of 100 parts by mass of dimethyl terephthalate and 70 parts by mass of ethylene glycol, and the mixture is gradually heated, and finally, at 220°C, an ester exchange reaction is carried out while distilling off methanol, to synthesize a precursor of polyethylene terephthalate. Next, 0.02 parts by mass of an 85% aqueous solution of phosphoric acid (molar concentration 14.6 mol / L) is added to the precursor, and the mixture is transferred to a polycondensation reaction vessel. The reaction system is gradually depressurized while heating and increasing the temperature in the polycondensation reaction vessel, and a polycondensation reaction is carried out at 290°C under a reduced pressure of 1 hPa, to obtain a polyester resin having a desired molecular weight. When particles are added, it is preferable to add a slurry in which particles are dispersed in ethylene glycol to the polycondensation reaction vessel so as to obtain a predetermined particle concentration, and then carry out the polycondensation reaction. The intrinsic viscosity and the amount of DEG are adjusted by the above-mentioned method.

[0052] Next, a preferred method for producing the electrode film of the present invention using a polyester resin will be specifically described.

[0053] First, polyester resins with adjusted intrinsic viscosities for the surface layer (A layer) and B layer are heated under reduced pressure or in a nitrogen atmosphere, and dried, for example, at 150°C for 5 hours, preferably until the moisture content in the resin is 50 ppm or less.

[0054] Thereafter, the polyester resins of both layers are fed to a lamination extruder to perform melt extrusion. When a vent-type twin-screw extruder is used, the drying step may be omitted. When a plurality of polyester resins are mixed and used, they may be mixed in a drying step to a predetermined mixing ratio, or the mixing ratio may be measured when feeding the resin to the extruder. The resin thus melt-extruded is filtered to remove foreign matter while in a molten state, the extrusion amount is measured with a gear pump, and the resin is laminated using a manifold or merging block for 2 or 3 layers, extruded as a laminated molten sheet from a T-die having a slit-shaped discharge port, and solidified in close contact with a cooling roll to obtain a cast film (unoriented film (unstretched film)). In order to improve the adhesion between the molten sheet and the cooling roll, it is usually preferable to adopt an electrostatic application adhesion method and / or a liquid surface coating adhesion method.

[0055] The cast film is biaxially stretched. First, the film is heated by a group of rolls heated to a temperature higher than the glass transition temperature of the polyester resin, for example, 90°C to 135°C, more preferably 100°C to 130°C, by heating the film with two or more infrared heaters for full width heating and end heating, and stretched 4.0 to 5.5 times in the film longitudinal direction (MD) to obtain a uniaxially oriented film (uniaxially stretched film). Next, the film is stretched 3.5 to 5.0 times in the film transverse direction (TD), preferably at a temperature higher than 100°C and lower than 130°C.

[0056] The film thus obtained is preferably subsequently heat-set in-line and / or off-line. Furthermore, if necessary, the film may be stretched again in MD and / or TD before or after heat-setting. The heat-setting temperature is preferably 220 to 245°C, more preferably 225 to 245°C in order to further improve the gas barrier property, and particularly preferably 230 to 245°C. The heat treatment time is usually 1 second to 1 minute. In addition, in this heat-setting step, the heat shrinkage properties can be adjusted by performing a relaxation treatment in the longitudinal direction and / or the transverse direction.

[0057] After the heat setting treatment, a polyester film with complete crystal orientation can be obtained by passing through a cooling zone at 100 to 200° C. For example, after heat setting, the film can be rapidly or slowly cooled, or an intermediate cooling zone can be provided to adjust the heat shrinkage stress.

[0058] The film may be coated as necessary. By forming a laminated film having an organic layer on the surface of the surface layer (layer A), the adhesion to the deposition layer or conductive layer can be improved. That is, the laminated film for an electrode of the present invention preferably has an organic layer on at least one surface of the biaxially oriented polyester film for an electrode.

[0059] The coating liquid for forming the organic layer is dissolved, emulsified or suspended in water in terms of explosion-proofing and environmental pollution. The organic layer can be formed by coating the biaxially stretched film after completion of crystal orientation or by coating the film before completion of crystal orientation and then stretching it, but the latter method is particularly preferred in order to more significantly exhibit the effects of the present invention. The coating method is not particularly limited, but it is preferred to coat using a roll coater, gravure coater, reverse coater, kiss coater, bar coater, etc. In addition, the coating surface may be subjected to corona discharge treatment in air or various other atmospheres before coating, as necessary.

[0060] The organic layer may contain, as necessary, antifoaming agents, coatable crosslinking agents, thickeners, organic lubricants, inorganic particles, antioxidants, ultraviolet absorbers, foaming agents, dyes, pigments, and the like.

[0061] A preferred embodiment of the battery of the present invention is a battery having the electrode film described above. By adopting this embodiment, it is possible to suppress the decrease in efficiency even if the operating temperature is increased, and even if a short circuit occurs due to a foreign object such as a nail, the continuation of the short circuit can be suppressed by thermal contraction of the film. By providing a metal layer on the electrode film, an electrode base material of a battery can be obtained, and a positive electrode or a negative electrode can be obtained by laminating a positive electrode material or a negative electrode material thereon. A basic structure of a battery can be made by forming a laminated structure of a positive electrode / separator and / or a solid electrolyte / negative electrode, and injecting an electrolyte solution into it as necessary. A preferred embodiment of the battery of the present invention is a battery having the electrode film described above. By adopting this embodiment, it is possible to obtain an electrode film that can improve battery performance such as high output and long life by obtaining stable resistance characteristics. EXAMPLES

[0062] [Method of measuring characteristic values] (1) Total thickness of the film Ten stacked test pieces were measured using a micrometer in accordance with JIS C2151 (2019). The measured thickness was divided by 10 to obtain the thickness at each measurement point, and the average thickness at each of the five measurement points in the width direction was used as the total thickness of the film.

[0063] (2) Lamination thickness The film cross-section is extracted by freeze-cutting using a microtome. Five cross-sections are cut out in the width direction of the film. The laminated parts are identified by observation of each cross-section using a scanning electron microscope (Hitachi Field Emission Scanning Electron Microscope (FE-SEM) S-4000), and the thickness of layer A and the lamination ratio are calculated from the average thickness values ​​of each layer in the five cross-sectional photographs taken. When there are two layers A, the average thickness of each layer A is listed in the table.

[0064] (3) Intrinsic viscosity (IV) Polyester resin or polyester film was dissolved in 100 mL of orthochlorophenol (solution concentration C = 1.2 g / mL), and the viscosity of the solution at 25°C was measured using an Ostwald viscometer. The viscosity of the solvent was also measured in the same manner. Using the obtained solution viscosity and solvent viscosity, [η] was calculated according to the following formula (C), and the obtained value was taken as the intrinsic viscosity (IV). ηsp / C=[η]+K[η]2·C····Formula (C) (Here, ηsp = (solution viscosity / solvent viscosity)-1, and K is the Huggins constant (assumed to be 0.343).)

[0065] In addition, when the solution in which the polyester resin or polyester film was dissolved contained insoluble matter such as inorganic particles, the solution was filtered and the mass was measured, and a correction was performed to determine the measured sample mass by subtracting the mass of the filtered residue from the measured sample mass.

[0066] The intrinsic viscosity of the surface layer (layer A) was measured by the above method using a razor blade placed perpendicularly on the film surface to scrape off a sample in accordance with the thickness of the laminate. Furthermore, for layer B, layer A was further scraped off to leave only layer B, and the sample was measured.

[0067] (4) Crystallinity of the entire film 5 mg of the film sample was weighed into a sample pan and measured using a differential scanning calorimeter (TA Instruments DSC Q100) by heating from 25°C to 300°C at a heating rate of 20°C / min. The crystallinity (Χc) was calculated from the differential scanning calorimeter chart obtained using the heat of fusion (ΔHm) and the heat of cold crystallization (ΔHc) according to the following formula. Χc=(ΔHm-ΔHc) / ΔHm0 Here, ΔHm0 was used as the heat of fusion of perfectly crystalline PET, 140.10 J / g.

[0068] (5) Three-dimensional center surface average roughness (SRa) The film surface was measured by the stylus method under the following conditions using a three-dimensional surface roughness meter ET4000AK (manufactured by Kosaka Laboratory Co., Ltd.). Samples were cut out from random locations, and the measurement was performed on three samples. The three-dimensional central surface average roughness (SRa) of the film was calculated from the average value of the measurements of the three samples. The three-dimensional central surface average roughness (SRa) (unit: nm) is a measurement value using a three-dimensional roughness meter that corresponds to the center line average roughness of JIS-B0601 (1994). Needle diameter 2μmR Needle pressure 10mg Measurement length 500μm Vertical magnification: 20,000 times CUT OFF 250μm Measurement speed 100μm / s Measurement interval: 5μm Record number: 80 Hysteresis width ±6.25nm Reference area 0.1mm 2 .

[0069] (6) Surface resistivity of vapor-deposited film After removing the surface layer for three revolutions from the roll of vapor-deposited film after winding, a film large enough to obtain a sample of at least 10 cm square was taken, and then cut into 10 cm square pieces. The cut pieces were left in an environment of a temperature of 25°C and a relative humidity of 65% for 24 hours, and then a voltage of 100 V was applied for 10 seconds in that environment, after which measurements were made using a digital ultra-high resistance / micro ammeter R8340A (manufactured by Advantest Corporation).

[0070] (7) Adhesion of evaporated film An adhesive prepared by mixing Toyo-Morton's "Adcoat" (registered trademark) 503 (AD503), hardener CAT-10, and ethyl acetate in a ratio of 100:5:100 mass% was applied to the deposition surface of the cut sample taken in the same manner as in (6) using a Mayer bar #12. After application, the sample was dried for 30 seconds in a hot air oven at 70°C, and then laminated to the corona-treated surface of a 60 μm-thick unstretched polypropylene film, and aged for 72 hours at 40°C using a hot air oven. The laminated sample was cut to a width of 15 mm, and the peel strength between the polypropylene film and polyester film was measured at a peel angle of 90° using Orientec's "TENSILON" (registered trademark) UCT-100 under an atmosphere of room temperature of 23°C and relative humidity of 65%. S:500g / 15mm width or more A: 400g / 15mm width or more, less than 500g / 15mm width B: 200g / 15mm width or more, 400g / 15mm width or less C: Less than 200g / 15mm width.

[0071] Next, the polyester film of the present invention will be specifically described with reference to examples. In the examples, "parts" refers to "parts by mass" unless otherwise noted.

[0072] [Production of polyethylene terephthalate] The polyethylene terephthalate resin was prepared as follows.

[0073] (1) Polyethylene terephthalate resin (PET-1~4) To a mixture of 100 parts by mass of dimethyl terephthalate and 61 parts by mass of ethylene glycol, 0.04 parts by mass of magnesium acetate and 0.02 parts by mass of antimony trioxide were added, and the temperature was gradually raised, and finally, at 220°C, an ester exchange reaction was carried out while distilling off methanol. Next, 0.020 parts by mass of an 85% aqueous solution of phosphoric acid was added to the ester exchange reaction product, and then the product was transferred to a polycondensation reaction vessel. Furthermore, the reaction system was gradually depressurized while heating and raising the temperature, and a polycondensation reaction was carried out at 290°C under a reduced pressure of 1 hPa by a conventional method to produce a polyethylene terephthalate resin, and then the intrinsic viscosity was adjusted by controlling the polymerization time by a solid-phase polymerization method. The intrinsic viscosity of 1.20 was designated PET-1, that of 0.85 was designated PET-2, that of 0.68 was designated PET-3, and that of 0.60 was designated PET-4.

[0074] (2) Particle Master When producing the polyethylene terephthalate (1) above, after the transesterification reaction, an ethylene glycol slurry of alumina particles having a median diameter (average particle diameter) of 0.15 μm measured by a laser diffraction / scattering particle size distribution analyzer LA-700 (manufactured by Horiba, Ltd.) was added, followed by a polycondensation reaction to obtain a particle master having a particle concentration of 1.5 mass% (hereinafter, "PET-5"). Also, an ethylene glycol slurry of agglomerated silica particles of 1.2 μm was added, followed by a polycondensation reaction to obtain a particle master having a particle concentration of 2.0 mass% (hereinafter, "PET-6"). The intrinsic viscosity of both particle masters was adjusted to 0.65.

[0075] (Examples 1 to 4, Comparative Examples 1 to 4) After the raw materials of the compositions shown in Tables 1 and 2 were vacuum-dried at a temperature of 180°C for 6 hours, the raw materials for layer B were fed to the main extruder, melt-extruded at 280°C, and filtered with a 30μm cut filter. The raw materials for layer A were fed to the sub-extruder, melt-extruded at 290°C, and filtered with a 14μm cut filter. Subsequently, these molten polymers were merged in a T-shaped composite die so that layers A and B had the laminated configuration shown in Tables 1 and 2, and the merged molten polymers were extruded into a sheet, which was cooled and solidified by electrostatic adhesion on a cooling drum with a surface temperature of 25°C. The unstretched (unoriented) PET film thus obtained was heated to 127°C and stretched in three stages in the longitudinal direction at 2.21 times in the first stage, 1.14 times in the second stage, and 2.30 times in the third stage to form a uniaxially stretched film. This film was stretched 3.8 times in the width direction while being heated to 112°C (transverse stretching). This film was introduced into hot air having temperatures in Tables 1 and 2, and heat-treated (heat-set) for 3 seconds without relaxation in the MD and TD directions, and then relaxed (relaxed) in the width direction at 150°C by 3.0% relative to the width of the film after TD stretching, and then cooled. In this way, polyester films shown in Tables 1 and 2 were finally obtained. The total thickness, thickness of Layer A, crystallinity, intrinsic viscosity, and surface roughness in the tables are values ​​for the film before deposition.

[0076] Aluminum was vapor-deposited on the polyester film thus obtained. The method of vapor-depositing aluminum was as follows: the film was set on the unwinding device of a continuous vacuum vapor-depositing machine, and the film was wound up by running it over a cooled metal drum. At this time, the continuous vacuum vapor-depositing machine was turned on for 10 -4 The pressure was reduced to below Torr, 99.99% pure aluminum metal was loaded into an alumina crucible from the bottom of the cooling drum, and the aluminum metal was heated and evaporated to deposit on the surface layer A, forming an aluminum film with a thickness of 1 μm. This process was repeated three times. Furthermore, when the polyester film had a three-layer structure, deposition was repeated three times on the opposite side in the same manner, forming 3 μm aluminum deposition films on both sides to obtain a deposition film.

[0077] Comparative Example 5 The raw materials having the composition shown in Table 2 were vacuum dried at 180°C for 6 hours, and then the raw materials for layer A were fed to the main extruder, melt-extruded at 280°C, and filtered through a 30 μm cut filter. The raw materials were then fed into a T-shaped die as a single-layer film, and the molten polymer was extruded into a sheet, which was cooled and solidified by electrostatic adhesion onto a cooling drum with a surface temperature of 25°C. Thereafter, a polyester film was obtained in the same manner as described in Example 1. Furthermore, a 3 μm aluminum vapor deposition film was formed on both sides in the same manner as in Example 1 to obtain a vapor deposition film.

[0078] The vapor-deposited films using the polyester films obtained in the Examples as substrates were excellent in adhesion to the vapor-deposited film and surface resistivity. On the other hand, the aluminum vapor-deposited films using the polyester films obtained in the Comparative Examples 1 to 5 as substrates were inferior. In particular, in the Comparative Examples 4 and 5, it is believed that cracks and peeling occurred in the metal layer due to bending during winding.

[0079] [Table 1]

[0080] [Table 2] [Industrial Applicability]

[0081] According to the present invention, it is possible to provide a biaxially oriented polyester film for batteries having improved resistance characteristics of an electrode sheet, which leads to improved battery performance such as high output and long life of the battery. The film can be suitably used particularly as an electrode film.

Claims

1. A biaxially oriented polyester film for electrodes, which is a multilayer film having a B layer mainly composed of polyester and a surface layer (A layer) mainly composed of polyester, and satisfies the following requirements (1) to (4). (1) The thickness of layer A is 0.1 μm or more and less than 1.5 μm. (2) The total thickness of the film is 1.5 μm or more and 15 μm or less. (3) The intrinsic viscosity (IV, unit dl / g) of layer A is 0.65 to 1.20 (4) The crystallinity of the entire film as determined by differential scanning calorimetry using the following method is 30.0~50.0% <Measurement method> Measure by heating from 25° C. to 300° C. at a temperature increase rate of 20° C. / min. The degree of crystallinity (Χc) is calculated from the obtained differential scanning calorimetry chart using the heat of crystalline fusion (ΔHm) and the heat of cold crystallization (ΔHc) according to the following formula. Χc=(ΔHm−ΔHc) / ΔHm0 Here, ΔHm0 is 140.10 J / g, which is the value of the heat of fusion of perfectly crystalline PET.

2. 2. The biaxially oriented polyester film for electrodes according to claim 1, wherein the intrinsic viscosities of at least one of the surface layers (layer A) and layer B satisfy the following relationship: Intrinsic viscosity of surface layer (layer A) > Intrinsic viscosity of layer B

3. 3. The biaxially oriented polyester film for electrodes according to claim 1, wherein at least one of the surface layers (A layer) has a three-dimensional center surface average roughness (SRa) of 40 to 80 nm.

4. 3. The biaxially oriented polyester film for an electrode according to claim 1, wherein at least one of the A layers contains particles containing Al element.

5. 3. A laminate film for an electrode, comprising the biaxially oriented polyester film for an electrode according to claim 1 or 2, and an organic layer on at least one surface of the biaxially oriented polyester film for an electrode.

6. An electrode comprising the biaxially oriented polyester film for electrodes according to claim 1 or 2.

7. A method for producing a biaxially oriented polyester film for electrodes, which is a multilayer film having a B layer mainly composed of polyester and a surface layer (A layer) mainly composed of polyester, and which satisfies the following requirements (a) to (d): (a) The thickness of layer A is 0.1 μm or more and less than 1.5 μm. (b) The total thickness of the film is 1.5 μm or more and 15 μm or less. (c) Layer A is formed by melt extruding a resin raw material having an intrinsic viscosity (IV, unit dl / g) of 0.65 to 1.

20. (d) The crystallinity of the entire film as determined by differential scanning calorimetry using the following method is 30.0~50.0% <Measurement method> Measure by heating from 25° C. to 300° C. at a temperature increase rate of 20° C. / min. The degree of crystallinity (Χc) is calculated from the obtained differential scanning calorimetry chart using the heat of crystalline fusion (ΔHm) and the heat of cold crystallization (ΔHc) according to the following formula. Χc=(ΔHm−ΔHc) / ΔHm0 Here, ΔHm0 is 140.10 J / g, which is the heat of fusion of perfectly crystalline PET.

Citation Information

Patent Citations

  • Film for secondary battery electrode

    JP1998040919A

  • Film for secondary battery electrode

    JP1998040920A

  • Biaxially oriented polyester film for power storage element electrode

    JP2014220187A